Comment on Time-reversal symmetry-breaking superconductivity - Adhikari, S. K. [UNESP] (American Physical Society (APS), 2001)
It is pointed out that erroneous Bardeen-Cooper-Schrieffer model equations have been used by Haranath Ghosh in his recent treatment of time-reversal symmetry-breaking superconductivity. Consequently, his numerical results are misleading, and his conclusions are not to the point.
Keywords: calculation; conductance; mathematical analysis; mathematical model; short survey; temperature dependence; time